Engineering of graphene/epoxy nanocomposites with improved distribution of graphene nanosheets for advanced piezo-resistive mechanical sensing. Issue 16 (4th April 2016) - Tung, Tran Thanh; Karunagaran, Ramesh; Tran, Diana N. H.; Gao, Boshi; Nag-Chowdhury, Suvam; Pillin, Isabelle; Castro, Mickael; Feller, Jean-Francois; Losic, Dusan
Abstract : Conductive nanostructured composites combining an epoxy and graphene have been explored for application as high-performance piezo-resistive mechanical sensor. Abstract : Conductive nanostructured composites combining an epoxy polymer and graphene have been explored for applications such as electrostatic-dissipative, anti-corrosive, and electromagnetic interference (EMI) shielding, stealth composite coating and specifically for sensors. For many of these applications, the limits of dispersion of graphene nanosheets and the interface between fillers and matrices have affected their electrical, structural and mechanical properties. To address these problems, we present the use of a dimethylbenzamide (DMBA)-based hardener to modify the surface of reduced graphene oxide (RGO) and create a 3D architecture with a micro-porous structure. DMBA is applied to provide two functions: one is to act as a stabilizer to avoid restacking of graphene sheets during the reduction process, and the second is to provide a linkage between RGO and epoxy for the formation of homogeneous nanocomposites. Thin films of conductive polymer graphene composites (CPCs) were prepared using a simple doctor blade method, while piezoresistive sensors were prepared by spraying to demonstrate their application for mechanical strain sensing. The electrical properties of the composites as a function of graphene fillers were shown to significantly increase from 10 12 Ω sq −1 for neat epoxy to 10 6 Ω sq −1 for 2 wt% RGO in epoxy composites, while the modulus calculated using nanoindentation exhibited a 43.3% enhancement from 3.56 GPa for epoxy to 6.28 GPa for the composites containing 2 wt% graphene. The results of piezo-resistive performance for mechanical strain sensing under both static and dynamic strain modes showed good sensitivity with a gauge factor (GF) of 12.8 and a fast response time of 20 milliseconds. A minor loading/unloading hysteresis loop after 1000 cycles indicated good reversibility and reproducibility of the sensors. Excellent reproducibility, long-term stability and reliability of the sensing devices are confirmed working without decay of sensitivity after a 6-month exposure to ambient atmosphere. The results obtained suggest that these types of piezo-resistive sensors based on RGO/epoxy CPCs due to their simple, scalable and low cost production could lead to the development of high-performance mechanical strain sensors for a broad range of applications including real-time monitoring, wearable electronics, and structural health monitoring (SHM).